2019
DOI: 10.1136/bmjpo-2019-000499
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death in critically ill paediatric patients in Japan: a retrospective multicentre cohort study

Abstract: ObjectivesThe primary objective is to clarify the clinical profiles of paediatric patients who died in intensive care units (ICUs) or paediatric intensive care units (PICUs), and the secondary objective is to ascertain the demographic differences between patients who died with and without chronic conditions.MethodsIn this retrospective multicentre cohort study, we collected data on paediatric death from the Japanese Registry of Pediatric Acute Care (JaRPAC) database. We included patients who were ≤16 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
8
1
2
Order By: Relevance
“…Table 4 shows the categories of final diagnosis at ICUs and PICUs. The occurrence of extrinsic disease was significantly higher in the tracheostomy group (29,16.0% versus 549, 9.8%; p < 0.01). Among intrinsic disease, respiratory disease was the leading diagnosis in the tracheostomy group, and its occurrence was significantly higher than in the no-tracheostomy group (72, 39.8% versus 1029, 18.4%; p < 0.01).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Table 4 shows the categories of final diagnosis at ICUs and PICUs. The occurrence of extrinsic disease was significantly higher in the tracheostomy group (29,16.0% versus 549, 9.8%; p < 0.01). Among intrinsic disease, respiratory disease was the leading diagnosis in the tracheostomy group, and its occurrence was significantly higher than in the no-tracheostomy group (72, 39.8% versus 1029, 18.4%; p < 0.01).…”
Section: Resultsmentioning
confidence: 81%
“…This was an epidemiologic study based on JaRPAC data. This study was subgroup analysis, by using JaRPAC data which was published by Ishihara T, et al [16]. Data concerning patients who had not undergone tracheostomy when admitted to the ICU or PICU were extracted from the database.…”
Section: Designmentioning
confidence: 99%
“…This was an epidemiologic study based on JaRPAC data. This study was subgroup analysis, by using JaRPAC data which was published by Ishihara T, et al [16]. study Data concerning patients who had not undergone tracheostomy when admitted to the ICU or PICU were extracted from the database.…”
Section: Designmentioning
confidence: 99%
“…In our study, 11.14% of the patients who applied to the PICU met the definition for CCI. Ishihara et al [ 18 ] determined CCI at a rate of 58.15% in their study considering the broad-framed chronic condition. Similarly, Walter et al [ 20 ] found the CCI rate to be 51%.…”
Section: Discussionmentioning
confidence: 99%
“…Prematurity and prolonged mechanical ventilation seem to be acceptable indicators of significant health complications as well as healthcare costs. In previous studies, cardiovascular and neuromuscular diseases have been reported as the most common cause of death in the critically ill pediatric patients [ 18 , 23 25 ]. Namachivayam et al [ 19 ] observed that children who died in PICU were ventilated longer than survivors (34 days [25–50] versus 31 days [20–47]; p = 0.014).…”
Section: Discussionmentioning
confidence: 99%